Les Formes De Relations Client-Fournisseur: Synthese Des Modeles Et Approches Theoriques - EL Boujnouni, Soukaina (European Scientific Journal, ESJ, 2018)
Customer-supplier cooperation is at the heart of industrial concerns, with new market constraints forcing companies to establish stable and lasting relationships with their various partners (Perrotin & Louberu, 1996). This paper focuses on the requirements of the development of inter-firm exchanges in an industrial environment at a micro level. In particular, we will analyze how client companies structure their relationships with their suppliers and vice versa, and develop mechanisms to control their actions in order to achieve their own goals. We will search through a non-exhaustive list of theoretical approaches to characterize the forms of customer-supplier relationships and the different factors influencing the nature of cooperation between firms. To understand this dynamic, we will then mobilize a theoretical framework of the inter-organizational literature to identify a set of factors favoring the stability and smooth running of an industrial relationship.